“Impossible to break into nice free stroll” Canadian Re-citations of Paris in Gail Scott’s My Paris - Rzepa, Agnieszka (Romanica Silesiana)
The narrator/writer of Gail Scott’s novel My Paris (1999) finds herself in an overdetermined urban space of contemporary Paris. The space, already multiply written and rich in cultural associations, is re-worked again in the fragmented “diary,” in which the narrator both echoes and contests her literary guides, primarily Gertrude Stein’s work and Walter Benjamin’s Arcades Project. Her Paris emerges as a re-citation of the Paris inscribed in those and other texts, reconfigured from a perspective marked by temporal remove, which is stressed in the novel. Scott explores multiple, criss-crossing spaces of the city: those of architecture, culture, race, gender, nationality. While the text’s concern is to move to and fro “across comma of difference,” and to avoid binary oppositions without obliterating the all-important comma, it politicises its postmodern concerns. The article explores the postcolonial dimension of Scott’s novel, which, though not necessarily foregrounded, provides an important conceptual thread of the text. The narrator, a bilingual Québécoise, considers spaces of alterity and otherness of Paris, explicitly relating them to Canadian national experience. From this perspective the enticement and impossibility of the unitary construct of a nation symbolised by the republics of France and the United States are explored. The postcolonial reflection is closely related to the notion of a non-unitary, nomad subject that emerges from the novel. Key words: Quebec novel in English, Gail Scott, postcolonial urban space, Paris in literature, postcolonial Canadian literature, experimental writing in Quebec.